2022
DOI: 10.3390/coatings12091339
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration, Mechanical Properties and Carbonation Kinetics of PP-Fiber-Reinforced Cement-Based Composites with CO2-Curing Treatment

Abstract: The development of sustainability and high toughness in cement-based composites with polypropylene (PP) fiber is becoming increasingly important for future buildings, while CO2-curing treatment at early ages is precisely a promising technique for it. The present work reported the carbon sequestration and the mechanical property variations of different cement-based composites with and without PP fiber, 10% silica fume, and varied w/b ratios of 0.25 and 0.18. Carbonation–hydration kinetics of CO2-cured cement-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several studies found in the literature are related to the potential for mineralizing carbon dioxide into concrete through carbonation curing of cement-based materials [27][28][29].…”
Section: Carbon Dioxide Uptake By Cement-based Materialsmentioning
confidence: 99%
“…Several studies found in the literature are related to the potential for mineralizing carbon dioxide into concrete through carbonation curing of cement-based materials [27][28][29].…”
Section: Carbon Dioxide Uptake By Cement-based Materialsmentioning
confidence: 99%
“…Silva et al [17] found promising results in the cement paste powder generated in the recycling process of concrete, which is a material composed mainly of hydrated cement, and was subjected to carbonation. Hu et al [18] found that the addition of polypropylene fibers enhanced the CO 2 uptake of cement-based materials subjected to the CO 2 -curing process. According to Xuan et al [19], the use of eggshell powder added to the Portland cement under carbonation-curing conditions improved the mechanical characteristics and durability of the cement-based materials.…”
Section: General Background On the Carbonation As A Stage In The Deca...mentioning
confidence: 99%
“…10 The ecofriendly choice and use of wood fibers in these composites will help in long-term carbon storage while improving the mechanical properties of the composites. 11 The potential of carbonated cured wood-geopolymer (such as SS)based composites, how they perform mechanically and thermally, will aid in establishing proper optimization processing methods for different applications. 12 In the presence of CO 2 , SS reacts to form silica gel with the subsequent removal of water to form a hardened glass material and a byproduct of sodium carbonate (Na 2 CO 3 ) and silica (SiO 2 ) as seen in chemical eq 1 and stoichiometric eq 2.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonation curing, which is the diffusion of CO 2 into the pores of a matrix, has been used in different studies with common uses in composites made of natural fibers like wood and cement to stabilize and improve the mechanical properties of the materials. Carbonation products formed during curing can fill the voids and pores of the composites improving densification and increasing the strength and durability of the composites . The ecofriendly choice and use of wood fibers in these composites will help in long-term carbon storage while improving the mechanical properties of the composites . The potential of carbonated cured wood-geopolymer (such as SS)-based composites, how they perform mechanically and thermally, will aid in establishing proper optimization processing methods for different applications .…”
Section: Introductionmentioning
confidence: 99%